Knight Launches Oasis Small- and Mid-Cap Algorithm (PR Newswire, 2009)
[...] readers are cautioned that any such forward-looking statements are not guarantees of future performance and are subject to certain risks, uncertainties and assumptions that are difficult to predict including, without limitation, risks associated with (i) the costs, integration, performance and operation of businesses recently acquired, or that may be acquired in the future, by the Company, and (ii) the closing of the sale of substantially all of the assets of the Asset Management business and costs and expenses associated with the Company's exit from the Asset Management business. Since such statements involve risks and uncertainties, the actual results and performance of the Company may turn out to be materially different from the results expressed or implied by such forward-looking statements.